Monitoring Political Parties’ Spending in Nigerian Elections: What Role for the Press and other Public Institutions? - Odunlami, Dele; Akinola, Lanre; Adetola, Obatunde Bright (NIU Journal of Social Sciences, 2020)
Aside from the Press in its sobriquet as the Fourth Estate of the realm of political governance, two principal institutions that are responsible for the monitoring of financial spending of political parties before, during and after general elections on behalf of the Nigerian State are the Independent National Electoral Commission (INEC) and Economic and Financial Crime Commission (EFCC). While the Electoral Act indeed specifies the spending limits for political parties and their candidates, the extent of compliance to the Electoral Act concerning finances by both political parties and their Monitors is of great concern in this paper. This is against the background of how billions of Naira meant for war prosecution against terrorism was said to have been misappropriated by Nigeriaâ€™s national government towards the 2015 General Elections. This paper reviews the roles of the press and other principal agents responsible for monitoring parties political campaigns spending in the last elections. It argues that in spite of the change mantra of new party that forms Nigeriaâ€™s national government after the old lost elections, the nature of party spending for elections in Nigeria is yet far from transparent and the roles of the public institutions saddled with the responsibility including the Press is called to question.  Keywords: Spending, Public Institutions, Elections, Parties, Governance.